Colposcopy in the Gynecology and Obstetrics Hospital of the Child - Rivas G., Mauro (2015)
251 has been selected patients colposcopic examinations of the External Advisory Services Obstetrics Gynecology Hospital for Children, being more prevalent in patients 21 to 40 years, equal incidence in pregnant and nonpregnant on equal presentation of processes colposcopic. The most frequent were: colpitis ectropion 77.7% and 78.1%. A case of microinvasive carcinoma was found in a patient with grade cytology 2. The percentage of benign images was 77.6% and 7.1% suspicious images.